Effect of Fe2B orientation on erosion–corrosion behavior of Fe–3.5 wt.% B steel in flowing zinc. (September 2015) - Wang, Yong; Xing, Jiandong; Ma, Shengqiang; Liu, Guangzhu; He, Yaling; Yang, Duoxue; Bai, Yaping
Highlights: Fe2 B boride in unidirectional solidified Fe–B steel possesses strong (0 0 2) texture. Orientation of Fe2 B has remarkably effect on erosion–corrosion resistance of Fe–B steel to flowing zinc. Pinning effect of corrosion product and oriented Fe2 B boride suppress erosion–corrosion. Abstract: The effect of Fe2 B orientation in Fe–3.5 wt.% B steel on its erosion–corrosion behavior in 460 °C flowing zinc was investigated. The results indicate that the erosion–corrosion resistance of Fe–3.5 wt.% B steel relies strongly on Fe2 B orientation. The orientation of Fe2 B determines the erosion–corrosion interface, which governs the diffusion, interfacial reaction, failure mode of Fe2 B, and significantly influences the erosion–corrosion behavior. The strong pinning effect of corrosion products and columnar Fe2 B suppresses erosion–corrosion; this suppression results in good erosion–corrosion resistance to liquid zinc of the Fe–3.5 wt.% B steel with the [0 0 2] direction of Fe2 B perpendicular to the erosion–corrosion interface.